The characteristics of oesophageal squamous cell carcinoma: an analysis of 1317 cases in southeastern China - Jiang, Yuan-Xi; Zhang, Dong-Wei; Chen, Ying; Sun, Hui-Hui; Xu, Shu-Chang; Gao, Heng-Jun (Contemporary Oncology/Współczesna Onkologia, 2015)
Material and methods : We retrospectively reviewed the ESCC cases in the biobank of the National Engineering Centre for Biochip in Shanghai, which cooperates with lots of hospitals and research institutions in southeastern China. The patients were pathologically confirmed as having ESCC. The demographic and histopathological features of these cases were analysed subsequently. Results : A total of 1317 patients were enrolled. The overall male : female ratio was 2.88 : 1. 74.34% of these cases occurred in people aged between 50–70 years. Dysphagia was the most common symptom, which accounted for 93.40% of all the patients. Stage II and III were predominant (79.73%). 72.89% of patients had a tumour length greater than 3 cm. Most of the tumours (65.83%) were located in middle third of the oesophagus. There was a significant difference among the tumour stage, length, and location in different sex groups (P 0.05). In males, ESCC is usually located in the lower parts, with a longer tumour length and higher tumour stage. 24.15% of patients had lymph nodes ratio (LNR) > 0.2. Conclusions : In our analysis, dysphagia was more common in ESCC patients, to whom more attention should be paid. Additionally, males had a higher incidence, with longer and more distant disease, which gives a poor prognosis.